Stiffness pulsation of the human brain detected by non-invasive time-harmonic elastography - Meyer, Tom; Kreft, Bernhard; Bergs, Judith; Antes, Erik; Anders, Matthias S.; Wellge, Brunhilde; Braun, Jürgen; Doyley, Marvin; Tzschätzsch, Heiko; Sack, Ingolf (Frontiers in Bioengineering and Biotechnology, 2023)
Cerebral pulsation is a vital aspect of cerebral hemodynamics. Changes in arterial pressure in response to cardiac pulsation cause cerebral pulsation, which is related to cerebrovascular compliance and cerebral blood perfusion. Cerebrovascular compliance and blood perfusion influence brain mechanical properties causing pulsation-induced changes in cerebral stiffness. However, there is currently no imaging technique available that can directly quantify the pulsation of brain stiffness in real time. Therefore, we developed non-invasive ultrasound time-harmonic elastography (THE) for real-time detection of brain stiffness pulsation. We used state-of-the-art plane-wave imaging for interleaved acquisitions of shear waves at a frequency of 60 Hz to measure stiffness and color flow imaging to measure cerebral blood flow within the middle cerebral artery. In a second experiment, we used cost-effective line-by-line B-mode imaging to measure the same mechanical parameters without flow imaging to facilitate future translation to the clinic. In ten healthy volunteers, stiffness increased during the passage of the arterial pulse wave from 4.8 ± 1.8% in the temporal parenchyma, to 11 ± 5% in the basal cisterns and to 13 ± 9% in the brain stem. Brain stiffness peaked in synchrony with cerebral blood flow at approximately 180 ± 30 ms after the cardiac R-wave. Line-by-line THE provided the same stiffness values with similar time resolution as high-end plane-wave THE, demonstrating the robustness of brain stiffness pulsation as an imaging marker. Overall, this study sets the background and provides reference values for time-resolved THE in the human brain as a cost-efficient and easy-to-use mechanical biomarker associated with cerebrovascular compliance.